Celebrity Persona: Can Intellectual Property Law in Indonesia Provide Adequate Protection? - Pamungkas, Ayu Mustika; Hulwanullah, Hikam (Jambura Law Review, 2025)
The vast economic turnover in the showbiz industry, which consistently involves numerous celebrities in merchandising activities as a form of product and service marketing, does not always yield positive impacts for the celebrities themselves. Numerous cases involve the unauthorized use of a celebrity persona, often resulting in legal disputes. This study aims to delve deeper into the legal protection of celebrity personas, particularly regarding their use by third parties, which may cause economic and moral losses for the persona owners. Employing normative legal research methods with a statute approach and conceptual approach, this research examines the issue from the perspective of intellectual property law in Indonesia. The study concludes that the protection of celebrity personas under intellectual property rights can be accommodated within copyright law by categorizing personas into "natural persona" and "created persona," enabling their protection under Indonesia's Copyright Act.